Platelet-derived chemokines in vascular biology - Hundelshausen, Philipp von; Petersen, Frank; Brandt, Ernst (Thrombosis and Haemostasis, 2007)
Undoubtedly, platelets are key elements in the regulation of thrombosis and haemostasis. Along with their primary task to prevent blood loss from injured vessels, platelets have emerged as regulators of a variety of processes in the vasculature. Multiple challenges, from the contact and adhesion to subendothelial matrix after injury of the vessel wall, to interactions with blood cells in inflammatory conditions, result in platelet activation with concomitant shape change and release of numerous substances. Among these, chemokines have been found to modulate several processes in the vasculature, such as atherosclerosis and angiogenesis. In particular, the chemokines connective tissue activating protein III (CTAP-III) and its precursors, or truncation products (CXCL7), platelet factor 4, (PF4, CXCL4) and its variant PF4alt (CXCL4L1) or regulated upon activation and normal T cell expressed and secreted (RANTES, CCL5), have been investigated thoroughly. Defined common properties as their aptitude to bind glycosaminoglycans or their predisposition to associate and form homooligomers are prerequisites for their role in the vasculature and function in vivo. The current review summarizes the development of these single chemokines, and their cooperative effects that may in part be dependent on their physical interactions.
Keywords: Chemokines; platelet immunology; atherosclerosis; angiogenesis and nhibitors